2020
DOI: 10.3389/fncel.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Spiking and Membrane Properties of Rat Olfactory Bulb Dopamine Neurons

Abstract: The mammalian olfactory bulb (OB) has a vast population of dopamine (DA) neurons, whose function is to increase odor discrimination through mostly inhibitory synaptic mechanisms. However, it is not well understood whether there is more than one neuronal type of OB DA neuron, how these neurons respond to different stimuli, and the ionic mechanisms behind those responses. In this study, we used a transgenic rat line (hTH-GFP) to identify fluorescent OB DA neurons for recording via wholecell electrophysiology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 92 publications
(160 reference statements)
2
16
0
Order By: Relevance
“…We also found that, when these neurons were grouped based on their neuronal areas (in which we classified them as either "Large" or "Small" dopamine neurons), the Large dopamine neurons produced more action potentials in response to weak current stimuli, while the Small neurons only produced a more phasic/single spiking response to these stimuli (Korshunov et al, 2020). When stimulated with stronger current stimuli, the Large and Small neurons both produced the same phasic/single spiking response (Korshunov et al, 2020). This difference in responses was likely due to inactivation properties of the voltage-gated Na + (Na V ) channels.…”
Section: The Spiking Profile Of Olfactory Bulb Dopamine Neuronsmentioning
confidence: 84%
See 4 more Smart Citations
“…We also found that, when these neurons were grouped based on their neuronal areas (in which we classified them as either "Large" or "Small" dopamine neurons), the Large dopamine neurons produced more action potentials in response to weak current stimuli, while the Small neurons only produced a more phasic/single spiking response to these stimuli (Korshunov et al, 2020). When stimulated with stronger current stimuli, the Large and Small neurons both produced the same phasic/single spiking response (Korshunov et al, 2020). This difference in responses was likely due to inactivation properties of the voltage-gated Na + (Na V ) channels.…”
Section: The Spiking Profile Of Olfactory Bulb Dopamine Neuronsmentioning
confidence: 84%
“…For example, none of the neurons from which we recorded displayed spontaneous spiking, only showing synaptically driven potentiation; this indicates a potential functional difference in the background activity between rat and mouse OB dopamine neurons, suggesting a possible functional and species difference (Pignatelli et al, 2005;Puopolo et al, 2005;Korshunov et al, 2020). We also found that, when these neurons were grouped based on their neuronal areas (in which we classified them as either "Large" or "Small" dopamine neurons), the Large dopamine neurons produced more action potentials in response to weak current stimuli, while the Small neurons only produced a more phasic/single spiking response to these stimuli (Korshunov et al, 2020). When stimulated with stronger current stimuli, the Large and Small neurons both produced the same phasic/single spiking response (Korshunov et al, 2020).…”
Section: The Spiking Profile Of Olfactory Bulb Dopamine Neuronsmentioning
confidence: 88%
See 3 more Smart Citations